A positive electrode active material and preparation method thereof, battery and electric device
The carbon layer of manganese vanadium ferrophosphate lithium cathode active material prepared by hydrothermal method and chemical vapor deposition method was solved, and the lithium battery cathode material's voltage platform and low conductivity was achieved, achieving the effect of high energy density and long cycle life.
Patent Information
- Application Number
- CN202211734198.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The current lithium battery positive electrode materials have low voltage platforms and low conductivity, resulting in low energy density and sharp attenuation of discharge capacity.
The hydrothermal method is used to prepare the positive electrode active material of manganese vanadium phosphate lithium iron phosphate, and the carbon layer is coated on the surface of the material through chemical vapor deposition to improve the conductive and rate performance of the material.
It improves the conductivity and rate performance of the positive electrode active material, extends the cycle life of the battery, and improves the stability of energy density and discharge capacity.
Smart Images

Figure CN116002651B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a positive electrode active material and a preparation method thereof, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are currently the most widely used high-performance energy storage devices that can be cyclically charged and discharged. The performance of lithium-ion batteries is largely determined by the performance of electrode materials. Excellent positive and negative electrode materials usually need to have advantages such as long cycle life, high reversible specific capacity, low synthesis cost, safety, no pollution, and reliable safety performance.
[0003] At present, lithium iron phosphate is the most widely commercialized lithium battery positive electrode material and is widely used in energy storage and commercial vehicles. However, due to the characteristics of the material itself, the voltage platform of lithium iron phosphate material is only about 3.3V, the platform is low, and the energy density is not high, which limits its use environment. The next generation material, lithium manganese iron phosphate / lithium manganese phosphate, has a relative Li+ / Li electrode potential that increases with the increase of manganese content, a high theoretical capacity density, and a low cost of raw materials for synthesizing lithium manganese phosphate, making it have great market prospects in the field of power supply. However, during the discharge process, too much Li+ will be embedded in the LiMn 2 O 4 In the 2 Mn 2 O 4 This situation occurs when the battery is discharged to 3V. At this time, the material changes from cubic phase to tetragonal phase, which leads to an increase in the unit cell volume. The electrode material collapses during the discharge cycle, causing the discharge capacity to decay sharply and Mn to dissolve seriously. In addition, both lithium manganese iron phosphate and lithium manganese phosphate have the problems of low conductivity, large DC resistance (DCR), and difficulty in fully utilizing the capacity. Summary of the invention
[0004] The present application provides a positive electrode active material and a preparation method thereof, a battery and an electrical device, which solve the problems of low voltage platform and low electrical conductivity of currently commonly used positive electrode active materials.
[0005] The method for preparing the positive electrode active material according to the first aspect of the present application comprises:
[0006] Adding a lithium source, a manganese source, a vanadium source, an iron source and a phosphorus source into a liquid medium and mixing them to obtain a positive electrode active material precursor solution;
[0007] The positive electrode active material precursor solution is transferred into a hydrothermal reactor in an oxygen-free gas atmosphere for reaction, cooled and filtered, washed, dried and crushed to obtain a powder material;
[0008] In an oxygen-free gas atmosphere, the surface of the powder material is coated with a carbon source by chemical vapor deposition, and then crushed to obtain a positive electrode active material.
[0009] Optionally, in other embodiments of the present application, in the step of transferring the cathode active material precursor solution into a hydrothermal reactor in an oxygen-free gas atmosphere, the reaction temperature is 100° C. to 200° C., and the reaction time is 2 h to 12 h.
[0010] Optionally, in other embodiments of the present application, the temperature of chemical vapor deposition is 650°C to 780°C.
[0011] Optionally, in other embodiments of the present application, the pressure of chemical vapor deposition is 80Pa-100Pa.
[0012] Optionally, in other embodiments of the present application, the deposition rate of chemical vapor deposition is 10 nm / min to 15 nm / min.
[0013] Optionally, in other embodiments of the present application, the deposition time of chemical vapor deposition is 10 min to 20 min.
[0014] Optionally, in other embodiments of the present application, the ratio of the coated mass of the carbon source to the mass of the positive electrode active material is 0.8% to 5%.
[0015] Optionally, in other embodiments of the present application, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium dihydrogen phosphate or lithium acetate.
[0016] Optionally, in other embodiments of the present application, the manganese source includes manganese sulfate.
[0017] Optionally, in other embodiments of the present application, the vanadium source includes vanadium sulfate.
[0018] Optionally, in other embodiments of the present application, the iron source includes one or more of ferrous sulfate, ferrous nitrate or ferrous chloride.
[0019] Optionally, in other embodiments of the present application, the phosphorus source includes one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate or lithium dihydrogen phosphate.
[0020] Optionally, in other embodiments of the present application, the carbon source includes one or more of citric acid, glucose, sucrose or polyethylene glycol.
[0021] Optionally, in other embodiments of the present application, the oxygen-free gas atmosphere includes one or more of nitrogen, argon or carbon dioxide.
[0022] Optionally, in other embodiments of the present application, the liquid phase medium includes one or more of deionized water, methanol solution, ethanol solution, acetone solution or polyol solution.
[0023] According to the positive electrode active material provided in the second aspect of the present application, the positive electrode active material is prepared by the above preparation method, and the positive electrode active material includes a core layer and a coating layer coated on the surface of the core layer; the core layer includes a compound with the chemical formula LiMn x V y Fe (1-x-1.5y) PO 4 , where 0 < x < 1, 0 < y < 2 / 3, and x + 1.5y < 1; the coating layer includes carbon element.
[0024] Optionally, in other embodiments of the present application, the positive electrode active material is in a granular shape, and the D50 of the positive electrode active material is 0.2 μm to 2 μm.
[0025] Optionally, in other embodiments of the present application, the thickness of the coating layer is 120 nm to 210 nm.
[0026] According to the battery provided in the third aspect of the present application, it includes a positive electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer provided on the positive electrode current collector, and the positive electrode active material layer includes the above positive electrode active material or the positive electrode active material prepared by the above preparation method.
[0027] According to the electrical device provided in the fourth aspect of the present application, it includes the above battery.
[0028] The preparation method of the positive electrode active material according to the embodiment of the present application has at least the following technical effects:
[0029] 1) The lithium iron vanadium manganese phosphate positive electrode active material prepared by the preparation method of the present application has excellent electrical conductivity and high rate performance;
[0030] 2) The present application uses a hydrothermal method to prepare the positive electrode active material, and the obtained positive electrode active material has small particles, controllable composition, stable microstructure and uniform element distribution;
[0031] 3) The present application adopts chemical vapor deposition for carbon coating. On the one hand, carbon coating can effectively improve the electron transmission efficiency of the positive electrode active material, reduce the powder resistance of the positive electrode active material, and thus improve the high-power discharge performance and fast charging capability of the battery made of the positive electrode active material; on the other hand, carbon coating can control the grain growth of the positive electrode active material, play a role in artificially controlling the microscopic morphology of the particles, and prevent the positive electrode active material from having a negative impact on its power and low temperature due to its excessive particle size. Compared with ordinary sintering, the chemical vapor deposition method adopted in the present application can make the coating layer on the surface of the core layer material more uniform, dense, and complete, thereby improving the rate, low temperature and cycle performance of the positive electrode active material. In addition, it can reduce the carbon stripping phenomenon during the crushing process of the positive electrode active material, reduce the free carbon content in the finished positive electrode active material, and improve the processing performance of the positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 It is a flow chart of the preparation method of the positive electrode active material provided in this application. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0035] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0036] The embodiments of the present application provide a positive electrode active material and a preparation method thereof, a battery and an electrical device. The following are detailed descriptions. It should be noted that the description order of the following embodiments is not intended to limit the preferred order of the embodiments.
[0037] The first aspect of the present application provides a method for preparing a positive electrode active material, such as Figure 1 As shown, including:
[0038] Step S1: adding a lithium source, a manganese source, a vanadium source, an iron source and a phosphorus source into a liquid medium, mixing them, and obtaining a positive electrode active material precursor solution;
[0039] Step S2: transferring the cathode active material precursor solution into a hydrothermal reactor in an oxygen-free gas atmosphere for reaction, cooling and filtering, washing, drying and crushing to obtain a powder material;
[0040] Step S3: In an oxygen-free gas atmosphere, the surface of the powder material is coated with a carbon source by chemical vapor deposition (CVD), and the positive electrode active material is obtained after crushing.
[0041] The present application adopts a hydrothermal method to prepare the positive electrode active material, and the obtained positive electrode active material particles are small, the composition is controllable, the microstructure is stable, and the element distribution is uniform; the present application adopts chemical vapor deposition for carbon coating, and the obtained coating layer is more uniform.
[0042] In some embodiments of the present application, in the reaction step of transferring the positive electrode active material precursor solution into a hydrothermal reactor in an oxygen-free gas atmosphere, the reaction temperature can be 100°C to 200°C, or 120°C to 180°C, or 130°C to 150°C; the reaction time can be 2h to 12h, or 5h to 10h, or 6h to 8h. The reaction temperature controls the reaction products (side reactions), reaction speed and uniformity. When the temperature is below 100°C, the solvent molecules in the solution are not sufficiently powered, and the gas phase cannot be effectively formed, and the ions cannot combine to form a complex. When the temperature is above 200°C, the solute molecules are active, driving the ions to combine rapidly, and it is easy to produce byproducts such as lithium manganese phosphate, lithium iron phosphate, and lithium vanadium phosphate. It is not easy to combine evenly to form a lithium manganese vanadium iron phosphate complex. When the temperature is between 100 and 200°C, a lithium manganese vanadium iron phosphate complex can be formed. Increasing the temperature can increase the reaction rate and reduce the required time, but lowering the temperature can make the generated complex product more uniform, so that the element distribution in the final product is stable and the degree of homogenization of each structure is high. The reaction time can affect the yield of the finished product and corresponds to the reaction temperature. The shorter the time required for the same yield when the temperature is increased, the longer the time at the same temperature, the more complete the reaction, and the higher the yield of the finished product. Therefore, the reaction temperature and time can be adjusted according to the required performance of the finished positive active material.
[0043] In some embodiments of the present application, the temperature of chemical vapor deposition can be 650°C to 780°C, 700°C to 770°C, or 730°C to 750°C. The vapor deposition temperature is affected by the type of carbon source on the one hand, and is related to the temperature required for the process of transformation of the material and the complex into a crystal on the other hand. When the temperature is too low, the carbon source cannot be effectively carbonized, organic matter remains, and the crystal cannot grow reasonably; when the temperature is too high, side reactions are likely to occur, and the iron ions in the material are oxidized to trivalent and then produce byproducts such as iron phosphide; when the temperature is in the range of 650 to 780°C, increasing the temperature can increase the material grain growth rate, thereby improving the overall production efficiency, but the fast growth rate will lead to an increase in the grain size, resulting in a decrease in the capacity, power and low-temperature performance of the finished positive active material, but the increase in grain size will improve the compaction performance of the material, so the temperature can be adjusted according to the required finished positive active material performance.
[0044] In some embodiments of the present application, the pressure of chemical vapor deposition can be 80Pa to 100Pa, or 85Pa to 95Pa, or 90Pa. The pressure of chemical vapor deposition affects the density of carbon coating and grain growth. If the pressure is too low, the coating effect is sparse; if the pressure is too high, the grains cannot grow effectively; the pressure of 80 to 100Pa is within a reasonable range. Within this range, increasing the pressure can increase the density of the coating, reduce the grain size, and improve the power and low-temperature performance of the finished positive active material, but it will reduce the compaction performance of the finished positive active material. Therefore, it can be adjusted according to the required performance of the finished positive active material.
[0045] In some embodiments of the present application, the deposition rate of chemical vapor deposition can be 10nm / min to 15nm / min, 11nm / min to 14nm / min, or 12nm / min to 13nm / min. The chemical vapor deposition rate affects the uniformity and completeness of the coating. Too slow will lead to too slow production time and too low efficiency; too fast will lead to uneven coating and inability to coat completely; 10nm / min to 15nm / min is a reasonable range. When the rate is reduced within this range, the uniformity and completeness of the coating will be improved, but the production efficiency will decrease. Therefore, it can be adjusted according to the required performance of the finished positive active material.
[0046] In some embodiments of the present application, the deposition time of chemical vapor deposition can be 10min to 20min, 13min to 18min, or 15min to 17min. The time of chemical vapor deposition is determined by the deposition rate and the carbon layer thickness required for the finished material. When the required carbon coating quality is high, that is, the carbon layer thickness is thick, the deposition time can be increased, or when the deposition rate is reduced at the same carbon layer thickness, the deposition time can also be increased, and vice versa. Therefore, it can be adjusted according to the required performance of the finished positive active material.
[0047] In some embodiments of the present application, the coating mass of the carbon source accounts for 0.8% to 5% of the mass of the positive electrode active material. The main function of carbon coating is to improve the conductivity of the material and control grain growth, but when the content is lower than 0.8%, both effects are not significant, and 5% is the limit value of this effect. When it is higher than 5%, there is no such effect and the carbon content is too high, which reduces the energy density of the material and makes the material processing difficult. Within the range of 0.8% to 5%, other conditions remain unchanged. A single increase in carbon coating can continuously improve the conductivity of the positive electrode active material, reduce the particle size of the positive electrode active material, and thus improve the power and low temperature performance of the positive electrode active material, but it will lead to a decrease in the compaction performance of the positive electrode active material and a decrease in the energy density, so it can be adjusted according to the desired performance of the finished positive electrode active material.
[0048] In some embodiments of the present application, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium dihydrogen phosphate or lithium acetate.
[0049] In some embodiments of the present application, the manganese source includes manganese sulfate.
[0050] In some embodiments of the present application, the vanadium source includes vanadium sulfate.
[0051] In some embodiments of the present application, the iron source includes one or more of ferrous sulfate, ferrous nitrate or ferrous chloride.
[0052] In some embodiments of the present application, the phosphorus source includes one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, or lithium dihydrogen phosphate.
[0053] In some embodiments of the present application, the carbon source includes one or more of citric acid, glucose, sucrose or polyethylene glycol.
[0054] In some embodiments of the present application, the oxygen-free gas atmosphere includes one or more of nitrogen, argon or carbon dioxide.
[0055] In some embodiments of the present application, the liquid medium includes one or more of deionized water, methanol solution, ethanol solution, acetone solution or polyol solution; the amount of the liquid medium is 5 to 10 times the total mass of the added lithium source, manganese source, vanadium source, iron source and phosphorus source.
[0056] In a specific implementation, the method for preparing the positive electrode active material includes:
[0057] 1) Weighing a soluble lithium source, a manganese source, a vanadium source, an iron source, and a phosphorus source in a certain molar ratio, pouring them into the liquid medium in sequence, stirring them on an automatic stirrer for 0.5-1h to mix them evenly, and obtaining a positive electrode active material precursor solution;
[0058] 2) Transfer the precursor solution of the positive electrode active material into a hydrothermal reactor under an anaerobic gas atmosphere, keep it at a temperature of 100 - 200 °C for 2 - 12 h, wait for it to cool to room temperature, filter to obtain a solid material, wash it with absolute ethanol, and then vacuum dry the material at a temperature of 100 - 200 °C for 2 - 10 h. Then, pulverize it, and the pulverization particle size D50 is 0.1 - 1 μm, which is the powder material;
[0059] 3) Uniformly coat the powder material with a carbon source by CVD chemical vapor deposition method. The temperature of chemical vapor deposition is 650 - 780 °C, the pressure is 80 - 100 Pa, the deposition rate of chemical vapor deposition is 10 - 15 nm / min, the deposition time is 10 - 20 min, and the mass ratio of the carbon source coating to the mass of the final positive electrode active material product is 0.8% - 5%. Grind and pulverize the coated material, and the pulverization particle size D50 is 0.2 - 2 μm to form the final positive electrode active material.
[0060] In the second aspect of the present application, a positive electrode active material is provided. The positive electrode active material is prepared by the above preparation method. The positive electrode active material includes a core layer and a coating layer coated on the surface of the core layer; the core layer includes a compound with the chemical formula LiMn x V y Fe (1-x-1.5y) PO 4 , where 0 < x < 1, 0 < y < 2 / 3, and x + 1.5y < 1; the coating layer includes carbon element. In the present application, a lithium iron vanadium manganese phosphate positive electrode active material is prepared. Its vanadium ions can form a stable (PO 5+ ) 4 ) 3- polyanion group through strong covalent bonds, and the oxygen atoms in the crystal lattice are not easily lost, having stable thermodynamic properties. In addition, due to the fact that the PO 4 tetrahedron and VO 6 octahedron in lithium iron vanadium manganese phosphate form a three-dimensional framework structure by sharing vertex oxygen atoms, the advantage of the structure is beneficial to the deintercalation and intercalation of Li + . Therefore, lithium vanadium phosphate has excellent electrical conductivity and high rate performance.
[0061] In some embodiments of the present application, the positive electrode active material is in a granular form, and the D50 of the positive electrode active material can be 0.2μm to 2μm, for example, 0.3μm, 0.6μm, 0.8μm, 0.9μm, 1.3μm, 1.7μm or a range consisting of any two numbers therein. In some embodiments, the particle size of the positive electrode active material can also be 0.5μm to 1.5μm; in some embodiments, the particle size of the positive electrode active material can also be 0.7μm to 1.0μm. D50 represents the value of the particle size corresponding to when the volume cumulative distribution percentage of the positive electrode active material reaches 50%, in μm. The present application adopts a hydrothermal method to prepare the positive electrode active material, and the obtained positive electrode active material particles are small, the composition is controllable, the microstructure is stable, and the elements are evenly distributed.
[0062] In some embodiments of the present application, the thickness of the coating layer can be 120nm to 210nm, for example, 130nm, 160nm, 180nm or a range consisting of any two numbers therein. In some embodiments, the thickness of the coating layer can also be 150nm to 200nm. In some embodiments, the thickness of the coating layer can also be 170nm to 190nm. The present application adopts chemical vapor deposition for carbon coating, and the thickness of the obtained coating layer is more uniform.
[0063] In addition, the third aspect of the present application provides a battery, including a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material or the positive electrode active material prepared by the above-mentioned preparation method.
[0064] In a specific implementation, the above-mentioned positive electrode active material is evenly mixed with a conductive agent, a binder and a solvent, and is made into a positive electrode sheet through processes such as screening, coating, rolling, slitting and cutting.
[0065] Specifically, the type of the conductive agent is not limited, and any known conductive agent can be used. Examples of the conductive agent may include, but are not limited to, carbon materials such as natural graphite, artificial graphite, Super P conductive carbon black, acetylene black, needle coke, carbon nanotubes, and graphene. The above positive electrode conductive agents can be used alone or in any combination.
[0066] The type of binder used in the manufacture of the positive electrode active material layer is not particularly limited. In the case of the coating method, it can be a material that is soluble or dispersible in the liquid medium used in the manufacture of the electrode. Examples of binders may include, but are not limited to, one or more of the following: polyethylene, polypropylene, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, etc. The above binders may be used alone or in any combination.
[0067] There is no restriction on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive agent, and the binder. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, water and a mixed medium of alcohol and water. Examples of organic media may include, but are not limited to, hexane, benzene, toluene, xylene, pyridine, acetone, tetrahydrofuran (THF), N-methylpyrrolidone (NMP), and the like.
[0068] Specifically, the battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the positive electrode sheet is the above-mentioned positive electrode sheet. In specific implementation, the above-mentioned positive electrode sheet is assembled into a lithium-ion battery with the negative electrode sheet, the separator and the electrolyte. The negative electrode material used in the negative electrode sheet can be one or more of artificial graphite, natural graphite, mesophase carbon microspheres, amorphous carbon, lithium titanate or silicon-carbon alloy. The negative electrode material also needs to have the characteristics of high compaction density, high mass specific capacity and high volume specific capacity.
[0069] A fourth aspect of the present application provides an electrical device comprising the above-mentioned battery.
[0070] In some embodiments, the electrical device of the present application is, but is not limited to, a backup power supply, a motor, an electric car, an electric motorcycle, a power-assisted bicycle, a bicycle, an electric tool, a large household battery, etc.
[0071] The following describes the invention in conjunction with specific embodiments.
[0072] Embodiment 1,
[0073] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0074] (1) Weigh 2.45 g of lithium hydroxide, 7.55 g of manganese sulfate, 3.90 g of vanadium sulfate, 3.04 g of ferrous sulfate, and 9.8 g of solid phosphoric acid, pour them into 150 ml of deionized water in sequence, stir them on an automatic stirrer for 1 h to mix evenly and completely dissolve them into a solution to obtain a positive electrode active material precursor solution;
[0075] (2) The positive electrode active material precursor solution was transferred into a hydrothermal reactor in an oxygen-free gas atmosphere, kept at 180° C. for 8 h, cooled to room temperature, filtered to obtain a solid material, washed with anhydrous ethanol, and vacuum dried at 120° C. for 5 h, and then the solid material was crushed to obtain a powder material with a particle size D50 of 0.2 μm;
[0076] (3) The powder material in step (2) is uniformly coated with a layer of carbon source using a CVD chemical vapor deposition device. The temperature of the chemical vapor deposition is 750°C, the pressure is 80 Pa, the deposition rate of the chemical vapor deposition is 10 nm / min, and the deposition time is 15 min. After completion, a uniform carbon layer with a thickness of 150 nm is deposited on the surface of the powder material. The coated material is ground and pulverized, and the pulverized particle size D50 is 0.5 μm to form a positive electrode active material.
[0077] Embodiment 2,
[0078] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0079] (1) Weigh 3.87 g of lithium carbonate, 6.04 g of manganese sulfate, 3.90 g of vanadium sulfate, 4.56 g of ferrous sulfate, and 14.9 g of ammonium phosphate solid, pour them into 200 ml of 50% ethanol solution in sequence, stir them on an automatic stirrer for 1 h to mix evenly and completely dissolve them into a solution to obtain a positive electrode active material precursor solution;
[0080] (2) The positive electrode active material precursor solution was transferred into a hydrothermal reactor in an oxygen-free gas atmosphere, kept at 160° C. for 6 h, cooled to room temperature, filtered to obtain a solid material, washed with anhydrous ethanol, and then vacuum dried at 100° C. for 6 h, and then the solid material was crushed to obtain a powder material with a particle size D50 of 0.1 μm;
[0081] (3) The powder material in step (2) is uniformly coated with a layer of carbon source using a CVD chemical vapor deposition device. The temperature of the chemical vapor deposition is 720°C, the pressure is 85 Pa, the deposition rate of the chemical vapor deposition is 12 nm / min, and the deposition time is 10 min. After completion, a uniform carbon layer with a thickness of 120 nm is deposited on the surface of the powder material. The coated material is ground and pulverized, and the pulverized particle size D50 is 0.2 μm to form a positive electrode active material.
[0082] Embodiment 3,
[0083] This embodiment provides a method for preparing a positive electrode active material, comprising the following steps:
[0084] (1) Weigh 10.39 g of lithium dihydrogen phosphate, 6.04 g of manganese sulfate, 3.90 g of vanadium sulfate, and 5.40 g of ferrous sulfate solid, pour them into 180 ml of 40% methanol solution in sequence, stir them on an automatic stirrer for 1.2 h to mix evenly and completely dissolve them into a solution to obtain a positive electrode active material precursor solution;
[0085] (2) The positive electrode active material precursor solution was transferred into a hydrothermal reactor in an oxygen-free gas atmosphere, kept at 200°C for 7 hours, cooled to room temperature, filtered to obtain a solid material, washed with anhydrous ethanol, and vacuum dried at 150°C for 4 hours. The solid material was then crushed to obtain a powder material with a particle size D50 of 0.3 μm.
[0086] (3) The powder material in step (2) is uniformly coated with a layer of carbon source using a CVD chemical vapor deposition device. The temperature of the chemical vapor deposition is 760°C, the pressure is 90 Pa, the deposition rate of the chemical vapor deposition is 15 nm / min, and the deposition time is 14 min. After completion, a uniform carbon layer with a thickness of 210 nm is deposited on the surface of the powder material. The coated material is ground and pulverized, and the pulverized particle size D50 is 0.7 μm to form a positive electrode active material.
[0087] Comparative Example 1
[0088] This comparative example provides a method for preparing a positive electrode active material of lithium manganese vanadium iron phosphate by a solid phase method, comprising the following steps:
[0089] (1) Weigh 129.28 g of ferric nitrate, 8.053 g of manganese sulfate, 3.1195 g of ammonium metavanadate, and 39.2 g of phosphoric acid, add deionized water to mix and dissolve, and then adjust the volume to 1 L (the molar concentration of the acid solution is about 0.4 M). Measure 200 ml of concentrated ammonia water, add deionized water to adjust the volume to 1 L (the molar concentration of the alkali solution is about 1 M), and pump the acid solution and the alkali solution into a stirred reactor filled with deionized water at a feed rate of 1 L / h, respectively. The reaction temperature is controlled to be 40°C, the stirring rate is 200 rpm, and the reaction pH value is about 2. After reacting for 1 hour, the precipitated product is taken out, washed several times, and then separated from the solid and liquid, placed in an oven at 80°C for drying for 5 hours, and pre-calcined at 300°C for 6 hours in a tubular furnace under inert atmosphere to obtain an iron vanadium manganese phosphate precursor material.
[0090] (2) Weigh 6 g of iron vanadium manganese phosphate precursor material, 1.6672 g of lithium hydroxide, and 0.6 g of sucrose, add 4 ml of deionized water, mix well, and dry in an oven at 80°C for 5 h. Put it into a tubular furnace and calcine it at 600°C for 12 h under inert atmosphere to obtain iron phosphate manganese vanadium lithium positive electrode material. The material is crushed to obtain the positive electrode active material. The crushed particle size D50 is 1.2 μm, and the carbon coating layer is about 150-280 nm (the thickness of the carbon coating layer between the positive electrode active material particles and in different directions of the particles obtained by this method is uneven, so the thickness is a range value).
[0091] Comparative Example 2
[0092] This comparative example provides a method for preparing a lithium iron phosphate LFP positive electrode active material under the same conditions as Example 2, comprising the following steps:
[0093] (1) Weigh 3.87 g of lithium carbonate, 12.91 g of ferrous sulfate, and 14.9 g of ammonium phosphate solid, pour them into 200 ml of 50% ethanol solution in sequence, stir them on an automatic stirrer for 1 h to mix them evenly and completely dissolve them into a solution to obtain a positive electrode active material precursor solution;
[0094] (2) The positive electrode active material precursor solution was transferred into a hydrothermal reactor in an oxygen-free gas atmosphere, kept at 160° C. for 6 h, cooled to room temperature, filtered to obtain a solid material, washed with anhydrous ethanol, and then vacuum dried at 100° C. for 6 h, and then the solid material was crushed to obtain a powder material with a particle size D50 of 0.1 μm;
[0095] (3) The powder material in step (2) is uniformly coated with a layer of carbon source using a CVD chemical vapor deposition device. The temperature of the chemical vapor deposition is 720°C, the pressure is 85 Pa, the deposition rate of the chemical vapor deposition is 12 nm / min, and the deposition time is 10 min. After completion, a uniform carbon layer with a thickness of 120 nm is deposited on the surface of the powder material. The coated material is ground and pulverized, and the pulverized particle size D50 is 0.2 μm to form a positive electrode active material.
[0096] Comparative Example 3
[0097] This comparative example provides a method for preparing a lithium manganese iron phosphate LMFP positive electrode active material under the same conditions as in Example 2, comprising the following steps:
[0098] (1) Weigh 3.87 g of lithium carbonate, 6.04 g of manganese sulfate, 6.84 g of ferrous sulfate, and 14.9 g of ammonium phosphate solid, pour them into 200 ml of 50% ethanol solution in sequence, stir them on an automatic stirrer for 1 h to mix evenly and completely dissolve them into a solution to obtain a positive electrode active material precursor solution;
[0099] (2) The positive electrode active material precursor solution was transferred into a hydrothermal reactor in an oxygen-free gas atmosphere, kept at 160° C. for 6 h, cooled to room temperature, filtered to obtain a solid material, washed with anhydrous ethanol, and then vacuum dried at 100° C. for 6 h, and then the solid material was crushed to obtain a powder material with a particle size D50 of 0.1 μm;
[0100] (3) The powder material in step (2) is uniformly coated with a layer of carbon source using a CVD chemical vapor deposition device. The temperature of the chemical vapor deposition is 720°C, the pressure is 85 Pa, the deposition rate of the chemical vapor deposition is 12 nm / min, and the deposition time is 10 min. After completion, a uniform carbon layer with a thickness of 120 nm is deposited on the surface of the powder material. The coated material is ground and pulverized, and the pulverized particle size D50 is 0.2 μm to form a positive electrode active material.
[0101] The positive electrode active materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into button batteries in a glove box, and the parameters such as slurry ratio and coating thickness were controlled to be the same. Then, the electrochemical performance was tested using a blue electric test system. The electrical performance test results are shown in Table 1:
[0102] Table 1
[0103]
[0104] It can be seen from Table 1 that, by comparing Examples 1 to 3 with Comparative Examples 1 to 3, the positive electrode active materials prepared in Examples 1 to 3 have excellent 0.1C gram capacity performance, far exceeding the LFP material of Comparative Example 2 and the LMFP material of Comparative Example 3; and the performance is more outstanding at high rates, indicating that the material has superior rate performance and conductivity; under normal temperature and 45°C high temperature cycles, the cycle retention rates of the positive electrode active materials prepared in Examples 1 to 3 are higher than those of Comparative Example 2, and much higher than those of Comparative Example 3, indicating that the positive electrode active material prepared in this application has better structural stability than LFP and LMFP materials, and has stable The thermodynamic properties of LMFP solve the problem of structural collapse and rapid capacity attenuation during the LMFP cycle process; and by comparing Examples 1 to 3 with Comparative Example 1, it can be seen that the 0.1C gram capacity performance and cycle retention rate of Examples 1 to 3 are higher than those of Comparative Example 1. Examples 1 to 3 are positive electrode active materials prepared by hydrothermal method and chemical vapor deposition method, while Comparative Example 1 is a positive electrode active material prepared by solid phase method, which shows that the positive electrode active material prepared by the method of the present application has smaller particles, stable microstructure, more uniform coating layer, and excellent conductive performance and cycle performance.
[0105] The present application adopts hydrothermal method and chemical vapor deposition method to prepare positive electrode active materials with small particle size and uniform distribution, excellent performance, high quality and stable structure, high voltage platform and energy density, thus solving the problems of low voltage platform of currently commonly used positive electrode active materials such as lithium iron phosphate and low conductivity of lithium iron manganese phosphate.
[0106] The above is a detailed introduction to a positive electrode active material and a preparation method thereof, a battery and an electrical device provided by the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a positive electrode active material, characterized in that: include: Adding a lithium source, a manganese source, a vanadium source, an iron source and a phosphorus source into a liquid medium and mixing them to obtain a positive electrode active material precursor solution; The positive electrode active material precursor solution is transferred into a hydrothermal reactor in an oxygen-free gas atmosphere for reaction, cooled and filtered, washed, dried and crushed to obtain a powder material; In an oxygen-free gas atmosphere, the surface of the powder material is coated with a carbon source by chemical vapor deposition, and the positive electrode active material is obtained after crushing; The temperature of the chemical vapor deposition is 650°C to 780°C; The pressure of the chemical vapor deposition is 80Pa to 100Pa; The deposition rate of the chemical vapor deposition is 10 nm / min to 15 nm / min.
2. The method for preparing a positive electrode active material according to claim 1, characterized in that: In the step of transferring the cathode active material precursor solution into a hydrothermal reactor in an oxygen-free gas atmosphere for reaction, the reaction temperature is 100° C. to 200° C., and the reaction time is 2 h to 12 h.
3. The method for preparing a positive electrode active material according to claim 1, characterized in that: The deposition time of the chemical vapor deposition is 10 min to 20 min.
4. The method for preparing a positive electrode active material according to claim 1, characterized in that: The ratio of the coated mass of the carbon source to the mass of the positive electrode active material is 0.8% to 5%.
5. The method for preparing a positive electrode active material according to claim 1, characterized in that: The lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium dihydrogen phosphate or lithium acetate; and / or, The manganese source comprises manganese sulfate; and / or, The vanadium source comprises vanadium sulfate; and / or, The iron source includes one or more of ferrous sulfate, ferrous nitrate or ferrous chloride; and / or, The phosphorus source includes one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate or lithium dihydrogen phosphate; and / or, The carbon source includes one or more of citric acid, glucose, sucrose or polyethylene glycol.
6. The method for preparing a positive electrode active material according to claim 1, characterized in that: The oxygen-free gas atmosphere comprises one or more of nitrogen, argon or carbon dioxide; and / or, The liquid medium includes one or more of deionized water, methanol solution, ethanol solution, acetone solution or polyol solution.
7. A positive electrode active material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The positive electrode active material includes a core layer and a coating layer coated on the surface of the core layer; the core layer includes a compound with the chemical formula LiMn x V y Fe (1-x-1.5y) PO4, where 0 < x < 1, 0 < y < 2 / 3, and x + 1.5y < 1; the coating layer includes carbon element.
8. The positive electrode active material according to claim 7, characterized in that The positive electrode active material is in a granular form, and the D50 of the positive electrode active material is 0.2 μm to 2 μm; and / or, The coating layer has a thickness of 120 nm to 210 nm.
9. A battery comprising a positive electrode plate, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material as described in any one of claims 7 to 8 or the positive electrode active material prepared by the preparation method as described in any one of claims 1 to 6.
10. An electrical device, characterized in that: Comprising the battery as claimed in claim 9.
Citation Information
Patent Citations
Manganese-iron-lithium phosphate material and preparation method thereof, battery paste, cathode and lithium battery
CN106816584A